GARBAGE TRUCKS - Dieker, Wendy Strobel (Mankato, Minnesota : Amicus/Amicus Ink, 2019)
This book invites early readers to look for new vocabulary words and pictures while giving simple facts about garbage trucks and how they pick up trash in order to keep communities clean.
Keywords: Refuse collection vehicles -- Children's nonfiction